Flambagem lateral com torção e distorção da alma em vigas de perfis I metálicos duplamente simétricos - Rossi, Alexandre (2018)
The lateral torsional buckling with web distortions is characterized by the combination of global buckling modes, lateral torsional buckling (LTB), with local buckling modes (LB) of the web. The analytical procedures, for beams with non-slender web, that are adopted in international standards and in the national standard NBR 8800:2008 don?t consider the effect of web distortion during the lateral torsional buckling. These procedures consider that the metal beams collapse occur through the pure FLT, that is, there isn't distortion of the cross section during the LTB. This fact differs from real situations mainly for cross sections with a web slenderness parameter close to Annex G's limit of the Brazilian Standard. In order to evaluate the effect of the web distortion on the reduction of the strength of steel I-beams with double cross section, a parametric study was carried out through numerical analysis in ABAQUS 6.12 and GBTUL 2.06 Software. For the development of the analysis, the numerical modeling was calibrated with experimental models available in the literature. By comparing the results obtained in the numerical analysis with the experimental results, it was possible to conclude that numerical modeling, through the ABAQUS Software - that uses Finite Element Method (FEM) - is a useful tool in the stability study of metal beams. After the calibration, analyzes were performed on several profiles, rolled and welded, to evaluate the effect of the web distortion. The influence of this distortion was examined by comparing the critical moments of the numerical analyzes of elastic stability with the critical moments of the normative procedures. Elastic stability analyzes were also validated by comparing the results of the ABAQUS Software 6.12 with the results of the GBTUL 2.06 Software, which uses the Generalised Beam Theory (GBT) formulations. The effects of initial geometric imperfection and residual stresses were also investigated. Through the comparison of the resistant moment characteristic of the geometric physical nonlinear analysis, with the resistant moment characteristic of the normative procedure, NBR 8800: 2008, it was possible to evaluate the effect of these imperfections on the resistance to FLTD of the metal beams. By performing numerical simulations in several Ibeams with variable web slenderness, it was concluded that the effect of this distortion on the reduction of the critical moment is more significant for beams that have shorter unlocked length and high web slenderness. In addition, it was observed that the effect of the web distortion was more pronounced for beams that present stocky flanges, that is, with less slenderness. Therefore, it was observed that the reduction of the critical moment due to the web distortion effect was significant. Lastly, adjustments were proposed for the procedure of calculation of resistant moment of I-beams with web non-slender, Annex G, of the Brazilian standard, NBR 8800: 2008. The effects of web distortion, initial geometric imperfection and residual stress were considered in the adjustments